THE PHENOMEN OF CORPORATE CULTURE OF PERSONALITY IN THE CONTEXT OF EDUCOLOGY KNOWLEDGES - Brovko, Kateryna (Educological discourse, 2017)
In the study the essence of the phenomenon of corporate culture of person from the point of view of philosophy, pedagogy, psychology, management is revealed. The structural elements of the corporate culture of personality (a system of material and spiritual values, predictions, beliefs, expectations, norms and behavioral style) and their significance are determined. The essence of the accumulative and productive, transformative, communicative functions of the corporate culture of personality with considering to management is revealed. The importance of the components of the corporate culture of personality (world outlook, corporate values, style of behavior, norms) is characterized. Indicators of the formation of the corporate culture of personality (motivation, development of partner interaction with other subjects of the organization, social stability, high organizational culture, degree of awareness, compliance with the ethics of corporate behavior) are determined. Factors influencing the process of formation of the corporate culture of personality are identified. The importance of the socio-psychological climate as an influence factor in the process of formation the corporate culture of personality is underlined. The information on the sources that contribute to the formation of the corporate culture of personality is presented. The importance of active inclusion of the head of organization in the process of formation the corporate culture of individual is revealed. Based on the analysis of scientific psychological literature, the essential characteristics of the term «socio-psychological climate» are characterized.